SCAI cardiogenic shock classification after out of hospital cardiac arrest and association with outcome. Issue 3 (23rd May 2020) - Pareek, Nilesh; Dworakowski, Rafal; Webb, Ian; Barash, Jemma; Emezu, Gift; Melikian, Narbeh; Hill, Jonathan; Shah, Ajay; MacCarthy, Philip; Byrne, Jonathan
Abstract: Objectives: We aimed to validate the Society for Cardiovascular Angiography and Interventions (SCAI) classification to evaluate association with outcome in a real‐world population and effect of invasive therapies. Background: Cardiogenic shock is common after Out of Hospital Cardiac Arrest (OOHCA) but is often multifactorial and challenging to stratify. Methods: The SCAI shock grade was applied to an observational registry of OOHCA patients on admission to our center between 2012 and 2017. The primary end‐point was 30‐day mortality and secondary end‐points were mode of death and 12‐month mortality. Provision of early CAG and mechanical circulatory support (MCS) was evaluated by SCAI shock grade using logistic regression. Results: Three hundred and ninety‐three patients (median age 64.3 years (24.9% females) were included. One hundred and seven patients (27.2%) were in Grade A, 94 (23.9%) in Grade B, 66 (16.8%) in Grade C, 91 (23.2%) in Grade D, and 35 (8.9%) in Grade E. There was a step‐wise significant increase in 30‐day mortality with increasing shock grade (A 28.9% vs. B 33.0% vs. C 54.5% vs. D 59.3% vs. E 82.9%; p < .0001). With worsening shock grade, requirement for renal replacement therapy and mortality from multiorgan dysfunction syndrome and cardiogenic causes increased. Early CAG was performed equally in all groups but was significantly associated with reduced mortality in SCAI grade D only (OR 0.26 [CI 0.08–0.91], p = .036). Conclusions: Increasing SCAI shock grade after OOHCA is associated with 30‐day mortality, requirement for renal replacement therapy and mortality attributed to multiorgan dysfunction syndrome and cardiac etiology death.